Esophagectomy complications and mortality in esophageal cancer patients, a comparison between transthoracic and trans-hiatal methods. Issue 2 (April 2019) - Aramesh, Mehdi; , Mohammad Shirkhoda; Hadji, Maryam; Seifi, Parisa; Omranipour, Ramesh; Mohagheghi, Mohammad Ali; Aghili, Mehdi; Jalaeefar, Amirmohsen; Yousefi, Nahid Karkhaneh; Zendedel, Kazem
No abstract available